URGENSI SISTEM E-VOTING DAN SIREKAP DALAM PENYELENGGARAAN PEMILU 2024 - Marzellina Hardiyanti; Praditya Arcy Pratama; Aura Diva Saputra; Mila Mar’atus Sholehah; M. Rizieq Aditya R (JOURNAL EQUITABLE, 2022)
Along with technological advances, there is a discourse about to use of a technology-based electoral system. Indonesia's geographical condition, which is not yet in all regions ready to hold technology-based elections, encourages integration between the E-Voting system and Sirekap. This research has 3 problems, namely (1) the urgency of the e-voting and Sirekap system in the 2024 general election, (2) the advantages and disadvantages of the e-voting and Sirekap system, and (3) efforts to integrate the e-voting and Sirekap system. in the administration of democratic elections. This study uses a juridical-normative method through a statutory approach and a descriptive-analytical analysis method. The results of this study state that the urgency of the need for the integration of the e-voting systems, among others, is that these two systems are considered capable of realizing accountability and transparency of vote counting during simultaneous elections. and Sirekap the process of sending ballots, while the weakness of these two systems is the uneven distribution of the internet network throughout Indonesia so that it can hinder the implementation of this electronic-based election. Efforts to integrate the e-voting and Sirekap systems are by combining these two systems based on the needs of each region.